Implementación de un proyecto eléctrico y domótico para vivienda campestre en el municipio de samaniego - Molina Mora, Jorge David; Bravo Pantoja, Didier Javier (Universidad Antonio Nariño, 2022)
The project emphasized two branches of action, the first focused on the design and construction of the electricity grid and its normal operation. The second one establishes the design and implementation of the project's home automation system. To consolidate the project, it was required to integrate several knowledge, establish the different options existing in the national market to implement the technological artifacts, all in conjunction with the commitment of the owner. This project allowed to deepen and appropriate new knowledge in the articulation of home automation systems and electrical regulations, which contributes to the consolidation of our professional projection in the implementation of industry 4.0 processes.